Algoritma Cellular Automata (CA) Dan Backtracking Untuk Simulasi Pencarian Jalan Pada Maze - Putra, Syopiansyah Jaya; Durachman, Yusuf; Huda, M. Qamarul (JIK: Jurnal Ilmu Komputer, 2008)
Human being wishes to finish problems and gain advantages as much as possible with efficiency of resources.The research discusses and compares the use of algorithms: back-tracking and cellular automata (CA) to look for the best way and solution. The main objective of this research is to learn the characteristic of CA and backtracking methos with their implementation at seeking walke at maze. It was found that CA method is more effective than backtracking method.Keywords:Ã‚Â  Cellular Automata (CA), Finite Automata (FA), Backtracking